Analysis of Phonetic Errors in Maharah Qira'ah Students of Mts Central Lampung - Intan Nur Asiyah; Erlina; M Afif Amrullah (PPPBA, 2025)
This study aims to analyze phonetic errors in reading skills (maharah qira’ah) among eighth-grade students of MTs Ma’arif 22 Bangunrejo, Central Lampung. The main problem addressed in this research is the low accuracy in pronouncing Arabic letters according to their makharijul huruf (articulation points) and phonetic features, which affects students’ comprehension of Arabic texts. This study employs a qualitative descriptive approach with data collected through observation, interviews, and documentation. The data were analyzed through the stages of reduction, display, and conclusion drawing. The findings reveal four main categories of phonetic errors: (1) errors in articulating adjacent letters, (2) errors in distinguishing similar phonetic features, (3) errors in pronouncing semivowels (mad and lin), and (4) fatal errors resulting from widely different sounds. Contributing factors include low learning motivation, non-religious educational backgrounds, regional dialect interference, and limited learning media and teaching variation. The study concludes that effective Arabic phonetic learning requires consistent pronunciation practice, short-text reading drills, and the integration of digital audio-visual media. The implications highlight the need for Arabic language teachers to develop contextual, communicative, and technology-based phonetic teaching strategies to minimize students’ phonetic errors effectively.